Evidence based HIV prevention strategic plan in a fragile setting: Mamfe Health District in focus - Julius, Mekolle, Enongene (My University, 2022)
An individual action is insufficient to stop HIV. Preventive measures must be tailored to the populations and countries they affect. This is particularly true in fragile contexts where persistent natural or man-made disasters pose a challenge to established health systems and policies. Effective HIV prevention programs can be created utilizing a well-considered combination of techniques to combat HIV transmission, and in this paper, I explore a number of strategies to motivate HIV preventative actions in Mamfe Health District.
Keywords: fragile setting; HIV; HIV prevention